Modeling Cutaneous Radiation Injury from Fallout. (31st August 2018) - Adams, Tim G.; Yeddanapudi, Neelima; Clay, Matthew; Asher, Jason; Appler, Jessica; Casagrande, Rocco
ABSTRACT: Objective: Beta radiation from nuclear weapons fallout could pose a risk of cutaneous radiation injury (CRI) to evacuating populations but has been investigated only cursorily. This work examines 2 components of CRI necessary for estimating the potential public health consequences of exposure to fallout: dose protraction and depth of dose. Methods: Dose protraction for dry and moist desquamation was examined by adapting the biological effective dose (BED) calculation to a hazard function calculation similar to those recommended by the National Council on Radiation Protection and Measurements for other acute radiation injuries. Depth of burn was examined using Monte Carlo neutral Particle version 5 to model the penetration of beta radiation from fallout to different skin tissues. Results: Nonlinear least squares analysis of the BED calculation estimated the hazard function parameter θ 1 (dose rate effectiveness factors) as 25.5 and 74.5 (Gy-eq) 2 h −1 for dry and moist desquamation, respectively. Depth of dose models revealed that beta radiation is primarily absorbed in the dead skin layers and basal layer and that dose to underlying tissues is small (<5% of dose to basal layer). Conclusions: The low relative dose to tissues below the basal layer suggests that radiation-induced necrosis or deep skin burns are unlikely from direct skin contamination with fallout. These results enable future modeling studies to better examine CRI risk and facilitate effectively managing and treating populations with specialized injuries from a nuclear detonation. ( Disaster Med Public Health Preparedness . 2019;13:463-469)